Loss and Gain in the Translation of Indonesian Novel Entitled “Cantik itu Luka” into “Beauty is a Wound” - Wijaya, I Made Exis; Gede Sosiowati, I Gst. Ayu; Widhiarcani Matradewi, Ni Ketut (Humanis, 2020)
The change of meaning in translation, either in the form of loss or gain, is inevitable. The change is influenced by several factors. This study aims to examine two problems concerning the matter of change of meaning in translation, especially in information loss and gain, by using Kurniawan’s novel, Cantik itu Luka , and its English version,  Beauty is a Wound as the reference. The first problem is about the loss and gain occurred in the translation, and the second is about the contributing factors. Both of the problems are analysed by using theory of translation. The first problem is analysed through the conception of loss and gain formulated by Larson (1998); the second is analysed with the conception of translation factor from Catford (1965). In collecting the data, the method used was documentation method, with note-taking technique. The comparison method is used in analysing the data. Based on the analysis that has been done, it can be concluded that loss appears mainly because of the replacement of the source language units with a cultural substitute or related equivalent that cannot represent the whole meaning components. Information gain appears from the change of implicit nuance of the source language unit into explicit, like in the modification of loan word. The contributing factors are both linguistic and cultural. The two factors intertwine with one another in influencing the loss and gain.